FAKTOR-FAKTOR YANG MEMENGARUHI TERJADINYA HIPERTENSI DI DAERAH PERKOTAAN (Analisis Data Riskesdas 2007) - Pradono, Julianty (GIZI INDONESIA, 2010)
FACTORS CONTRIBUTE TO HYPERTENSION IN RURAL AREAS(Data Analysis of Basic Health Research 2007)The increasing of blood-pressure is a one main risk factor to stroke and heart diseases. Blood-pressure increased could be caused by genetic factor, as well as beha viour and environment which might triggered the risk factor. This was much worst with the absence of the particular symptoms, therefore the increasing of blood-pressure was unrealized and could be resulted a very serious impact. Some studies shown that hypertension prevalens were continously rising in a young age group. This analysis aimed to identify factors influenced the rising of blood-pressure for preventing effort. Data sources for this study were Basic Health Research (Riskesdas) 2007. Blood-pressure was measured by using Digital Sphygmoma-nometer. The sample size consisted of 18,601 respondents, included age above 15 years old both males and females from 10 percent of urban area in Indonesia. A multivariate analysis had been done for describing factors influenced the blood-pressure increased. The results shown that respondents ≥ 45 years were the most contributed factor for the inceasing of blood-pressure (OR=2,4), followed by overweight-obese (OR=2,3), obese-central (OR=1,6), hyperglychemic (OR=1,5), duration of smoking (OR=1,5), mental disorder (OR=1,3), economic status (OR=1,2), and unmarried status (OR=1,2). On the otherhand, the better consumption grilled foods, and foods with preservatives might reduce the bloodpressure of respondents (anova, p=0,000). Prediction asumption towards blood-pressure based on those factors was 16,0 percent (R-squared). This study showed that lifestyle modification is essential in preventing urban adults from hypertension. Targeting adults with promotional efforts Healthy Behavior to raise awareness of risk factors for hypertension.Keywords: factors, hypertention, urban